2017
DOI: 10.1016/j.vaccine.2017.10.099
|View full text |Cite
|
Sign up to set email alerts
|

Selection of vaccine strains for serotype O foot-and-mouth disease viruses (2007–2012) circulating in Southeast Asia, East Asia and Far East

Abstract: Foot-and-mouth disease (FMD) is endemic in Southeast Asia (SEA) and East Asia with circulation of multiple serotypes and multiple genotypes within each serotype of the virus. Although countries like Japan and South Korea in the Far East were free of FMD, in 2010 FMD serotype O (O/Mya-98) outbreaks were recorded and since then South Korea has experienced several FMD outbreaks despite regular vaccination. In this study a total of 85 serotype O FMD viruses (FMDV) isolated from 2007 to 2012 from SEA, East Asia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 43 publications
(52 reference statements)
1
40
0
Order By: Relevance
“…The role of nt and aa substitutions in virulence and/ or immunity response needs more investigation. The increased number of detected substitutions indicates the presence of many serotypes and subtypes that increase the potential for genetic recombination and creation of new variant strains [28] . Continued studies by next generation sequencing are recommended for the detection of new subtypes, tracking the source of infection, and updates in control strategy and vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The role of nt and aa substitutions in virulence and/ or immunity response needs more investigation. The increased number of detected substitutions indicates the presence of many serotypes and subtypes that increase the potential for genetic recombination and creation of new variant strains [28] . Continued studies by next generation sequencing are recommended for the detection of new subtypes, tracking the source of infection, and updates in control strategy and vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination was not carried out in any of the goat and mixed farms, meaning that there is no clear evidence about the effectiveness of the vaccines utilized in the current outbreak. Vaccine match tests against isolates of Ind2001d sublineage showed that the O/PanAsia‐2 and O/IND/R2/75 vaccines matched well with the Ind2001d sublineage isolates (Mahapatra et al, , ). However, vaccine match tests between the O/PanAsia‐2 vaccine strain used in Jordan and the O/JOR/1/2017 isolate have not yet been carried out.…”
Section: Discussionmentioning
confidence: 99%
“…During an outbreak, prevention of FMD from spreading can be done with the help of emergency vaccinations. There is continuous development of new vaccines but it is labor and difficult to develop a new vaccine whenever a new virus appears [52,53,54]. Therefore, many kinds of research have been conducted to develop advanced vaccines that can respond to evolving versions of the virus [55,56].…”
Section: De-population Of Infected Animalsmentioning
confidence: 99%
“…Therefore, many kinds of research have been conducted to develop advanced vaccines that can respond to evolving versions of the virus [55,56]. Current problems with FMD vaccines include antigens losses during the process of purification, unable to maintain the antibodies, low immunogenicity and narrow protection range of the antigens [57]. Economic impact of FMD FMD is a highly contagious Transboundary animal disease which effects the clovenhoofed animals.…”
Section: De-population Of Infected Animalsmentioning
confidence: 99%